ISOLASI DAN KARAKTERISASI BAKTERI RESISTEN TEMBAGA DARI PANTAI TIMUR SURABAYA - Wahyu Irawati (Universitas Medan Area, 2019)
Copper pollution in the East Coast of Surabaya is one of the serious cases of heavy metal pollution in Indonesia. Pollution at this location has been proven to result in fish deaths and brain damage of local residents because they consume too much copper-contaminated fish. Copper bioremediation using indigen bacteria isolated from polluted environments is a promising solution to overcome copper pollution problems. Bacteria that commonly live in polluted environments can be isolated and used as copper bioremediation agents. This study aims to do: 1) isolation and characterization of copper resistant bacteria from the East Coast of Surabaya, 2) resistance testing of bacterial isolates, and 3) copper accumulation and biosorbtion tests of bacterial isolates. The bacterial isolates were characterized by the morphology of the colonies and their cells based on Gram staining. Resistance testing is done by determining Minimum Inhibitory Concentration/MIC. The accumulation test is carried out by separating the cell and growth medium, then each of them is distructed using HNO3. The results of isolation and characterization obtained six isolates of copper-resistant bacteria, namely PmbC1, PmbC2, PmbC3, PmbC4, PmbC5, and PmbC6 with MIC = 3 mM - 5mM CuSO4. PmbC4 isolate is the most resistant bacteria with the MIC of 5 mM and is capable of accumulating copper of 6.25 mg per gram of cell dry weight and biosorbtion of 92.17%.